Bonding strength of bamboo reinforcement in concrete – a systematic literature review (SLR) - Siti Khadijah Che Osmi; Adib Ngadenin; Norazman Mohamad Nor; Hapsa Husen; Muhamad Azani Yahya; Norhasliyah Mohamad Daud (Penerbit Universiti Kebangsaan Malaysia, 2021)
Towards sustainable environmental goals, the utilization of agricultural waste as concrete material in the low-cost construction industry has received special interest from many researchers. It is the best approach in converting waste into valuable sustainable products which consequently reduces abundant of the waste and avoid environmental pollution. Literature proved that bamboo has high tensile strength and the mechanical properties of bamboo are almost similar to steel reinforcement, besides the advantage of its lightweight and cost-effective. In this study, a Systematic Literature Review (SLR) is conducted to review the behaviour of the bonding strength of bamboo reinforcement in concrete. The SLR is proposed based on the widely adopted review protocol named ‘Reporting standards for Systematic Evidence Syntheses’ (ROSES). The proposed SLR procedure is critically discussed, starting from the formulation of the research question until the process of data abstraction and analysis. Particular emphasis is given on the different types of behaviour of bonding strength developed in bamboo reinforced concrete based on results of the pull-out test. Different types and behaviour of bamboo bonding reinforcement are studied and discussed. The study highlights the mechanical properties of bamboo as an alternative reinforcement in concrete and types of bamboo reinforced structural components. This reviews also compared the methodology adopted for surface treatment and preparation of bamboo reinforcement.